PUBLIC PROJECT OWNERSHIP IN AIN BEIDA: ANALYSIS OF CHALLENGES AND IMPROVEMENT PERSPECTIVES FOR A COHERENT CITY - Lazhar AS; Mohamed Chérif ADAD (International Journal of Innovative Technologies in Social Science, 2024)
Urban coherence is a crucial element for the sustainable development of cities. In Algeria, public project ownership plays an essential role in achieving this objective. This article examines the impact of public project ownership on urban coherence in Ain Beida, Algeria, by identifying the challenges it faces and proposing solutions to improve its performance. The study reveals that project ownership practices have a significant impact on the quality of life and urban development in Ain Beida and identifies avenues to enhance urban coherence. The study emphasizes the importance of training, effective communication, stakeholder involvement, and the adoption of agile methods to improve project ownership performance and urban coherence.